Mapping International University Partnerships Identified by East African Universities as Strengthening Their Medicine, Nursing, and Public Health Programs - Aaron N. Yarmoshuk; Anastasia Nkatha Guantai; Mughwira Mwangu; Donald C. Cole; Christina Zarowsky (Ubiquity Press, 2017)
Background International university partnerships are recommended for increasing the capacity of sub-Saharan African universities. Many publications describe individual partnerships and projects, and tools are available for guiding collaborations, but systematic mappings of the basic, common characteristics of partnerships are scarce. Objective To document and categorize the international interuniversity partnerships deemed significant to building the capacity of medicine, nursing, and public health programs of 4 East African universities. Methods Two universities in Kenya and 2 in Tanzania were purposefully selected. Key informant interviews, conducted with 42 senior representatives of the 4 universities, identified partnerships they considered significant for increasing the capacity of their institutions' medicine, nursing, and public health programs in education, research, or service. Interviews were transcribed and analyzed. Partners were classified by country of origin and corresponding international groupings, duration, programs, and academic health science components. Findings One hundred twenty-nine university-to-university partnerships from 23 countries were identified. Each university reported between 25 and 36 international university partners. Seventy-four percent of partnerships were with universities in high-income countries, 15% in low- and middle-income countries, and 11% with consortia. Seventy percent included medicine, 37% nursing, and 45% public health; 15% included all 3 programs. Ninety-two percent included an education component, 47% research, and 24% service; 12% included all 3 components. Conclusions This study confirms the rapid growth of interuniversity cross-border health partnerships this century. It also finds, however, that there is a pool of established international partnerships from numerous countries at each university. Most partnerships that seek to strengthen universities in East Africa should likely ensure they have a significant education component. Universities should make more systematic information about past and existing partnerships available publicly.